Urban Transportation and Marketing Efficiency among Tomato Marketers in OYO State, Nigeria - Idiaye, Chuks O; Oluwatayo, Isaac Busayo; Tijani, Nafisat O (ASEAN Marketing Journal, 2025)
The study examined the effect of urban transportation on tomato marketing efficiency using major markets in Ibadan metropolis in south-west Nigeria as case study. The data used were collected from a total of 170 tomato marketers using a structured questionnaire. The locations of the markets included Ibarapa Central, Ibarapa East, Ibarapa North, Ido, Lagelu, and Akinyele. Descriptive statistics, Shepherd’s measure of efficiency and Multinomial regression were used to analyze the data collected. Findings from the study revealed that transportation plays a crucial role in the marketing of tomato in Oyo state, Nigeria and that mini-cabs are the most preferred means of transportation amongst the tomato marketers. Also, it was found that, on average, the sampled tomato marketers were 38% market efficient, implying that the majority of the tomato marketers were operating at a relatively low level of efficiency. The study recommended that government agencies invest in improved urban transportation systems to moderate costs and other constraints that might be experienced in the course of tomato marketing activities.